TYPES OF REMODELING VESSELS OF DIFFERENT CALIBER IN ARTERIAL HYPERTENSION - Задорожная, Марина Петровна; Разумов, Владимир Валентинович (Medicine in Kuzbass, 2019)
Arterial hypertension is inevitably accompanied by remodeling of the heart and blood vessels, the study of which is characterized by the ambiguity of the research methods that prevent understanding of this phenomenon as a single process in the cardiovascular system. The aim of the study – to study the remodeling of arteries in the concept of their remodeling types, similar to the left ventricle, by duplex duplex scanning of peripheral arteries of different calibres to 154 patients (23 controls and 131 individuals with arterial hypertension). The manifestation of the reorganization of the arteries has been revealed already at the 1 stage of arterial hypertension, characterized by the caliber of mediated remodeling types with their greatest representation in large vessels that gravitate toward eccentric hypertrophy. Arteries of a smaller caliber showed a tendency to concentric remodeling. A gradual increase in the intensity of remodeling of the arteries was accompanied by the preservation of the regularities revealed already at the stage 1 of the disease.